A vaccine based on the yeast-expressed receptor-binding domain (RBD) elicits broad immune responses against SARS-CoV-2 variants - Liu, Yu; Zhao, Danhua; Wang, Yichang; Chen, Zhian; Yang, Li; Li, Wenjuan; Gong, Yanqiu; Gan, Chunmei; Tang, Jieshi; Zhang, Tizhong; Tang, Dan; Dong, Xiuju; et al. (Frontiers in Immunology, 2022)
Development of safe and efficient vaccines is still necessary to deal with the COVID-19 pandemic. Herein, we reported that yeast-expressed recombinant RBD proteins either from wild-type or Delta SARS-CoV-2 were able to elicit immune responses against SARS-CoV-2 and its variants. The wild-type RBD (wtRBD) protein was overexpressed in Pichia pastoris, and the purified protein was used as the antigen to immunize mice after formulating an aluminium hydroxide (Alum) adjuvant. Three immunization programs with different intervals were compared. It was found that the immunization with an interval of 28 days exhibited the strongest immune response to SARS-CoV-2 than the one with an interval of 14 or 42 days based on binding antibody and the neutralizing antibody (NAb) analyses. The antisera from the mice immunized with wtRBD were able to neutralize the Beta variant with a similar efficiency but the Delta variant with 2~2.5-fold decreased efficiency. However, more NAbs to the Delta variant were produced when the Delta RBD protein was used to immunize mice. Interestingly, the NAbs may cross react with the Omicron variant. To increase the production of NAbs, the adjuvant combination of Alum and CpG oligonucleotides was used. Compared with the Alum adjuvant alone, the NAbs elicited by the combined adjuvants exhibited an approximate 10-fold increase for the Delta and a more than 53-fold increase for the Omicron variant. This study suggested that yeast-derived Delta RBD is a scalable and an effective vaccine candidate for SARS-CoV-2 and its variants.